COVID-19 vaccination and HIV transmission among persons who inject drugs during the first two years of the COVID-19 pandemic in New York City - Don C. Des Jarlais; Chenziheng Allen Weng; Jonathan Feelemyer; Courtney McKnight (BMC, 2023)
Abstract Background To examine COVID-19 vaccination and HIV transmission among persons who inject drugs (PWID) during the COVID-19 pandemic (2020-2022) in New York City (NYC). Methods Two hundred and seventy five PWID were recruited from October 2021 to September 2022. A structured questionnaire was used to measure demographics, drug use behaviors, overdose experiences, substance use treatment history, COVID-19 infection, vaccination, and attitudes. Serum samples were collected for HIV, HCV, and SARS-CoV-2 (COVID-19) antibody testing. Results Participants were: 71% male, the mean age was 49 (SD 11), 81% reported at least one COVID-19 immunization, 76% were fully vaccinated and 64% of the unvaccinated had antibodies for COVID-19. Self-reported injection risk behaviors were very low. HIV seroprevalence was 7%. Eighty-nine percent of the HIV seropositive respondents reported knowing they were HIV seropositive and being on antiretroviral therapy prior to the COVID-19 pandemic. There were two likely seroconversions in 518.83 person-years at risk from the March 2020 start of the pandemic to the times of interviews, for an estimated incidence rate of 0.39/100 person-years, 95% Poisson CI 0.05-1.39/100 person-years. Conclusions There is concern that the COVID-19 pandemic disruptions to HIV prevention services and the psychological stress of the pandemic may lead to increased risk behavior and increased HIV transmission. These data indicate adaptive/resilient behaviors in both obtaining COVID-19 vaccination and maintaining a low rate of HIV transmission among this sample of PWID during the first two years of the COVID-19 pandemic in NYC.